With our Clipped Wings: a research-based performance on gay men's identities devised through narrative portraiture. Issue 2 (2nd April 2020) - Rodríguez-Dorans, Edgar
ABSTRACT: With our Clipped Wings is a performance that showcases the research findings of the doctoral research project "Understanding gay men's identities through narratives of their erotic and romantic relationships." The performance delivers compelling narratives through which participants in this research described in their own words what being gay means to them. It offers an intimate opportunity to observe the ways in which gay men have been trapped in oppressive social dynamics, environments, and discourses that have facilitated sexual encounters but have clipped their wings to love.